Factors in the Teaching of MAPEH and Performance of Grade 9 Learners in Gingoog City Division - Dime, Lilibeth S.; Pasion, Rodelio B. (Randwick International of Education and Linguistics Science Journal, 2025)
This study explored the extent to which specific factors influence the teaching of MAPEH (Music, Arts, Physical Education, and Health) and the corresponding academic performance of Grade 9 learners in the North 3 District, Gingoog City Division. Employing a sequential explanatory mixed-methods design, the study integrated quantitative data from 145 surveyed students with qualitative insights from interviews with 6 MAPEH teachers. Key factors investigated included teaching quality, classroom atmosphere, learner interest, parental support, and availability of resources. Statistical analysis revealed significant yet weak positive correlations between teaching-related factors and student performance. Notably, high levels of student interest and parental support emerged as critical contributors to learner achievement, while inadequate resources and physical infrastructure posed significant instructional barriers. Language barriers and insufficient MAPEH teacher expertise were also identified as limiting factors. Despite these challenges, many learners demonstrated proficiency or advanced performance levels. The study culminated in the development of a multi-pronged intervention program aimed at enhancing resource allocation, teacher training, classroom engagement strategies, and stakeholder involvement to improve MAPEH outcomes. These findings underscore the importance of a holistic and well-supported educational environment in delivering effective MAPEH instruction.